Genetic control of diameter and bark percentage in spotted gum (Corymbia spp.): can we breed eucalypts with more wood and less bark?. Issue 1 (2nd January 2020) - Paludeto, João Gabriel Zanon; Bush, David; Estopa, Regiane Abjaud; Tambarussi, Evandro Vagner
Abstract : This study aimed to estimate the genetic parameters of diameter at breast height over bark (DBHOB), bark percentage (Bark%) and the correlation between DBHOB and Bark% for Corymbia spp. Three independent trials were evaluated during this study: C. variegata (CV) and mixed spotted gum species (CMSG) were progeny trials measured at 4-years of age, and mixed Corymbia species (CSPP) from different seed sources measured at 3-years of age. The CV and CMSG mainly comprised of C. variegata, while the CSPP consisted of C. torelliana, C. maculata and C. citriodora progenies. There were significant differences between the progenies for the two traits evaluated in the three trials. The narrow sense heritability found for CMSG and CV were 0.55 and 0.42, respectively, for Bark% and 0.24 DBHOB in both trials. In CSPP, we found 0.21 for DBHOB, and a lower narrow-sense heritability for Bark% (0.19), since in this trial a significant part of the genetic variation is due to differences between seed sources. Genetic correlations (ranging from -0.18 to -0.47) between DBHOB and Bark% were indicated, i.e. as DBHOB increases, bark proportion decreases. We concluded that both traits, especially Bark%, are under significant genetic control in the Corymbia genus, making them good candidates for breeding programmes. This study provides valuable information about the genetic control of Bark%, which will be useful in further studies with other species, and the growth potential of the Corymbia genus as well. Future studies could ascertain the growth potential of Corymbia species, genetic control of bark in other important commercial species, determine the effect of bark thickness along the length of the stem (bark taper), and bark volume as a proportion of overall stem volume.